An affair to remember. (Economist, 2015)
An editorial is presented on the theft and public release of a large volume of personal data from Ashley Madison, an Internet firm allowing individuals to meet for the purpose of having an extramarital affair, saying the episode highlights the fact that many corporations and government bodies have inadequate computer security. The hacking group Impact Team and Ashley Madison's parent company, Avid Life Media, are cited.